Monocyte to high‐density lipoprotein cholesterol and lymphocyte to monocyte ratios are predictors of in‐hospital and long‐term mortality in patients with acute coronary syndrome. Issue 5 (7th January 2021) - Oylumlu, Muhammed; Oylumlu, Mustafa; Arik, Baran; Demir, Muhammed; Ozbek, Mehmet; Arslan, Bayram; Acun, Baris; Polat, Nihat; Akil, Mehmet Ata; Bilik, Mehmet Zihni
Abstract: Objective: We aimed to determine the relationship between LMR and MHR and in‐hospital and long‐term mortality in patients with ACS. Methods: We retrospectively collected patients with ACS undergoing coronary angiography between January 2012 and December 2013. Results: In total, 825 patients with a mean age of 62.4 ± 12.9 years (71.3% male) were enrolled in the study. Patients were divided into three tertiles based on MHR levels and LMR levels. In‐hospital mortality of the patients was significantly higher amongst patients in the upper MHR tertile when compared with the lower and middle MHR tertile groups [30 (10.9%) vs 8 (2.9%) and 14 (5.1%); P  < .001, P  = .009, respectively]. Five‐year mortality of the patients was significantly higher amongst patients in the upper MHR tertile when compared with the lower and middle MHR tertile groups [84 (30.5%) vs 48 (17.5%) and 57 (20.7%); P  < .001, P  = .005, respectively]. In‐hospital mortality of the patients was significantly higher amongst patients in the lower LMR tertile when compared with the upper and middle LMR tertile groups [25 (9.1%) vs 10 (3.6%) and 17 (6.2%); P  = .007, P  = .130, respectively]. Five ‐year mortality of the patients was significantly higher amongst patients in the lower LMR tertile when compared with the upper and middle LMR tertile groups [77 (28.0%) vs 47 (17.1%) and 65 (23.6%); P  = .001, P  = .142, respectively]. Conclusion: We have shown that high MHR and low LMR were significant and independent predictors of in‐hospital and long‐term mortality in patients with ACS.